The story of the Soudan. [(Told from the Parliamentary Papers)] (Freethought Publishing Company, 1885)
The atheistic platform, 5, p. 66-80. Facsimile reprint: New York, Kelley, 1970. (Rare social & political pamphlets). In: Annie Besant, A selection of the social and political pamphlets.